EVALUATION OF FLEXIBLE PAVEMENT DAMAGE USING THE PCI (PAVEMENT CONDITION INDEX) METHOD BASED ON CORE DRILL DATA. â€œCASE STUDY: ON THE MANDARIN ROAD TO THE PRESIDENT NICOLAO LOBATO ROUNDABOUT AND THE BEBONUK ROAD IN DILI CITY, TIMOR-LESTEâ€ - Brigida Abreu Freitas de Almeida; Krisnamurti Krisnamurti; Akhmad Hasanuddin; Anik Ratnaningsih (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
Localization and characterization of road damage are used in an effort to accelerate road repairs.Â The evaluation results were compared with field data and laboratory data.Â The results of the analysis show that the average PCI on the right side of the road reaches a value of 68 with a good rating good,Â on the left side it is worth 62 with a good rating good,Â and for the Bebonuk road section it is worth 39 with a bad rating poor.Â The average value of core drill is 86.85% and 99.92%,Â while the average PCI value is 35.36%.Â Asphalt content extracted with specifications 0.3,Â JMF 5.4% and penetration of 5.1%.